DAMPAK PROSOSIAL DAN KOMITMEN AFEKTIF PADA PERUBAHAN: IDENTIFIKASI ORGANISASI SEBAGAI VARIABEL MEDIASI - Azani, Arif Rahmat; Sirait, Elbriyan; Elyanis, Rafidah; Zaitul, Zaitul (Gapenas Publisher, 2025)
This study aims to examine the relationship between prosocial impact, organizational identification, and affective commitment to change among public sector employees. Using a quantitative approach with a cross-sectional survey design, data were collected from 41 employees of the West Sumatra Class II Land Transportation Management Office (BPTD). The research model tested four main hypotheses using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that prosocial impact has a significant positive effect on organizational identification, while it does not directly influence affective commitment to change. However, organizational identification significantly affects affective commitment to change and serves as a mediating variable between prosocial impact and affective commitment. These findings highlight the critical role of organizational identification in strengthening employees’ emotional support for organizational change. The study provides theoretical insights by reinforcing Social Identity Theory and Relational Job Design, and offers practical implications for public organizations to enhance commitment through meaningful work and identity-building strategies.